Audit Studies: Behind the Scenes With Theory, Method, and Nuance 2018
DOI: 10.1007/978-3-319-71153-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Hiring Discrimination: An Overview of (Almost) All Correspondence Experiments Since 2005

Abstract: This chapter aims to provide an exhaustive list of all (i.e. 90) correspondence studies on hiring discrimination that were conducted between 2005 and 2016 (and could be found through a systematic search). For all these studies, the direction of the estimated treatment effects is tabulated. In addition, a discussion of the findings by discrimination ground is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 101 publications
4
189
1
3
Order By: Relevance
“…More concretely, we add interactions with indicators of high-educated candidates, male candidates, candidates who reveal engagement in a cancer organisation, candidates who reveal engagement at a korfball sports club, candidates with two engagements, and candidates with three engagements. For both call-back outcomes, we find a significant interaction only with respect to gender: the male volunteering premium in terms of getting any positive reaction (an 15 While the size of our sample is substantially lower than the size of the data gathered in some recent large-scale correspondence experiments in the United States such as Kroft et al (2013) and Neumark et al (2015), it is at least comparable to many other recent (and well-published) field experiments included in the review study of Baert (2017). In addition, a post hoc power analysis shows that based on the variation in our dataset, we were able to distinguish rather small effects from zero effects.…”
supporting
confidence: 45%
See 1 more Smart Citation
“…More concretely, we add interactions with indicators of high-educated candidates, male candidates, candidates who reveal engagement in a cancer organisation, candidates who reveal engagement at a korfball sports club, candidates with two engagements, and candidates with three engagements. For both call-back outcomes, we find a significant interaction only with respect to gender: the male volunteering premium in terms of getting any positive reaction (an 15 While the size of our sample is substantially lower than the size of the data gathered in some recent large-scale correspondence experiments in the United States such as Kroft et al (2013) and Neumark et al (2015), it is at least comparable to many other recent (and well-published) field experiments included in the review study of Baert (2017). In addition, a post hoc power analysis shows that based on the variation in our dataset, we were able to distinguish rather small effects from zero effects.…”
supporting
confidence: 45%
“…In contrast to many former correspondence experiments in which applications were sent to vacancies in only one or a few specific occupations (with, potentially, a high (or low) treatment effect) (Baert, 2017), 4 we aimed to test the returns to volunteering with respect to hiring chances in multiple occupations (and, in relation to this, multiple sectors). Therefore, we created pairs of application templates (comprised of a résumé and a motivation letter) for jobseekers at two education levels.…”
Section: Application Templatesmentioning
confidence: 99%
“… Although fake-résumé audit studies sometimes find anti-female bias, often they find no bias or bias in favor of women (Baert, 2018). The findings with respect to gender are much more mixed than those for race/ethnicity.…”
Section: Challenges To the Discrimination Explanation For Stem Gendermentioning
confidence: 98%
“…Numerous studies have found wage and employment gaps between migrants and natives, which may at least partially be due to discrimination (Rinne 2012), particularly in the hiring decisions of firms (e.g., Baert 2017;Carlsson 2010;Weischelbaumer 2016). However, research also show major variations in the attitudes and behavior of employers as demonstrated in a study by Lundborg and Skedinger (2016) that identify significant heterogeneity in the attitudes of Swedish employers toward hiring, job performance, wage setting, and discrimination.…”
Section: The Demand-sidementioning
confidence: 98%
“…Anonymous job applications may be a way to combat employment discrimination (for an overview see, Baert 2017). In Sweden, a study by Åslund and Skans (2012) in the local public sector in the city of Gothenburg showed that anonymous job applications increased the chances of advancing to interviews for both women and immigrants of nonwestern origin.…”
Section: The Demand-sidementioning
confidence: 99%